2023
DOI: 10.3390/su15065197
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Underground Mining-Induced Fault-Influenced Rock Movement and Its Application

Abstract: The F317 fault, as a major tectonic zone in the Jianshan mine area, influences the geotectonic features and geomechanical properties of the mine area. Mining operations need to be conducted within these tectonic systems, so it is important to fully study and understand the characteristics and evolution of these tectonic systems to develop reasonable mining plans and safety measures. Aiming at the problem that the existence of the F317 fault affects the stability of the west road during the mining of the securi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Considering the above analysis, it can be concluded that the F22 fault is a nonwater-conducting fault. 2017; Dong et al 2023;Teng et al 2023;Zhou et al 2023). In this study, based on the typical profile of the V-Prospecting line near the F22 fault where the V-1 borehole is located (Fig.…”
Section: Analysis Of Water Conductivity Of F22 Faultmentioning
confidence: 99%
“…Considering the above analysis, it can be concluded that the F22 fault is a nonwater-conducting fault. 2017; Dong et al 2023;Teng et al 2023;Zhou et al 2023). In this study, based on the typical profile of the V-Prospecting line near the F22 fault where the V-1 borehole is located (Fig.…”
Section: Analysis Of Water Conductivity Of F22 Faultmentioning
confidence: 99%